Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Pada PT. Kerta Rajasa Raya Mojokerto - Wahyu Eko Pujianto; Afifatus Solikhah; Supriyadi Supriyadi (Program Pascasarjana (S2-Ilmu Manajemen) Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2022)
Organizational citizenship behavior (OCB) is a behavior is done voluntarily and can provide a positive contribution to the organization. This study aims to determine the effect of organizational commitment and job satisfaction partially and simultaneous on organizational citizenship behavior (OCB) employees at PT.Kerta Rajasa Raya Mojokerto. This research used a quantitative approach The total sample of 70 respondents employees at PT.Kerta Rajasa Raya Mojokerto. The research indicated that the organizational commitment have a positive influence and partial significant against organizational citizenship behavior (OCB) at PT. Kerta Rajasa Raya Mojokerto, Job satisfaction have a positive influence and partial significant against organizational citizenship behavior (OCB) at PT. Kerta Rajasa Raya Mojokerto, and Is the positive and significant between variables organizational commitment and Job Satisfaction simultaneously on variables organizational citizenship behavior (OCB) at PT.Kerta Rajasa Raya Mojokerto. The results showed that the variable organizational commitment and job satisfaction partially had a positive and significant effect on organizational citizenship behavior (OCB) and simultaneous the two independent variables also had a positive and significant effect on organizational citizenship behavior (OCB) employees at PT.Kerta Rajasa Raya Mojokerto